2009
DOI: 10.1364/oe.17.003124
|View full text |Cite
|
Sign up to set email alerts
|

Repetition rate stabilization of the SBS Q-switched fiber laser by external injection

Abstract: Repetition rate fluctuation is one of the main drawbacks of the low-threshold stimulated Brillouin scattering (SBS) Q-switched fiber laser. A method to stabilize the repetition rate is proposed in this paper by injecting a square-wave modulated light. It is measured experimentally that variance of the repetition rate can be improved from ~20% to ~1% of the period. It is also found that effectiveness of the method depends on modulation frequency and duty cycle of the injection. Its working mechanism is analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Brillouin fiber-ring cavity laser is a well-known laser configuration that has been intensively studied due to important features such as a narrow linewidth, low threshold power, gain quality of the nonlinear effect, and the easy experimental configuration [1]- [4]. These characteristics can be used for developing applications such as multiline lasers for temperature sensing [5] or gyroscopes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Brillouin fiber-ring cavity laser is a well-known laser configuration that has been intensively studied due to important features such as a narrow linewidth, low threshold power, gain quality of the nonlinear effect, and the easy experimental configuration [1]- [4]. These characteristics can be used for developing applications such as multiline lasers for temperature sensing [5] or gyroscopes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Say, it was shown that jittering of SBS-pulses fades with increasing intra-cavity loss [20]. Also, it was proposed to use a pulsed distributed feed-back (DFB) laser as source of stable pulsed seed signal for igniting SBS pulses [27]; in this case, SBS-boosting of the seed pulses occurs in a multi-pass amplifying regime; this allows jitter mitigating but not its elimination. However, the inclusion of additional expensive elements into the scheme leads to the loose of simplicity and increases the cost of such lasers but does not fully resolve the problem.…”
mentioning
confidence: 99%
“…The signal processor consists of an analog to digital converter (ADC) acquisition card and personal computer (PC) based software platform. The homemade seeder laser outputs 30-mW power with a linewidth of less than 5 kHz at 1540 nm [18] . The seeder is modulated by AOM and amplified by multi-stage fiber amplifier, as described in detail in Ref.…”
mentioning
confidence: 99%
“…Through 2048 points FFT, the IF is measured to be 56. 18 MHz with standard deviation of 0.033 MHz. And the IF is also stable with the environment temperature variations of ±10 • .…”
mentioning
confidence: 99%